Standardizing Catch Per Unit Effort (CPUE) of Coryphaena hippurus in the Southern Java Waters Using Generalized Additive Model (GAM) - Vianta Mandhalika; Bambang Semedi; Abu Bakar Sambah; Amin Setyo Leksono (Postgraduate, University of Mataram, 2025)
: Improving catch data through the standardization of catch per unit effort (CPUE) is crucial in providing accurate information for fish stock assessments. This study aims to develop a CPUE standardization model for dolphinfish (Coryphaena hippurus) in the Southern Java Waters. The analysis is based on historical dolphinfish catch data collected between 2019 and 2023. Bias in the CPUE data was reduced using the generalized additive model (GAM) approach. The results indicate that all explanatory variables significantly influence CPUE standardization. The combination of fishing duration, location, and period parameters proved effective in standardizing CPUE. The GAM-based standardization method successfully reduced variability in nominal CPUE, producing more consistent data. These results can provide an essential scientific basis for developing a sustainable management strategy for the Indian Ocean dolphinfish.